The Point Zoro Symmetric Single-Step Procedure for Simultaneous Estimation of Polynomial Zeros. (13th June 2012) - Monsi, Mansor; Hassan, Nasruddin; Rusli, Syaida Fadhilah
Abstract : The point symmetric single step procedure PSS1 has R -order of convergence at least 3. This procedure is modified by adding another single-step, which is the third step in PSS1. This modified procedure is called the point zoro symmetric single-step PZSS1. It is proven that the R -order of convergence of PZSS1 is at least 4 which is higher than the R -order of convergence of PT1, PS1, and PSS1. Hence, computational time is reduced since this procedure is more efficient for bounding simple zeros simultaneously.